Influence of structural features and feruloylation on fermentability and ability to modulate gut microbiota of arabinoxylan in in vitro fermentation - Li, Zhongxia; Zhang, Huibin; He, Li; Hou, Yaqin; Che, Yingjuan; Liu, Tian; Xiong, Shaobai; Zhang, Xuguang; Luo, Shunjing; Liu, Chengmei; Chen, Tingting (Frontiers in Microbiology, 2023)
Introduction Arabinoxylan (AX) is a versatile polysaccharide that shows various effects in modulating gut microbiota and health. The influence of arabinoxylan carbohydrate structural feature and feruloylation on fermentability and the effect of modulation of gut microbiota of AX was not clear. Methods Arabinoxylans from rice bran and corn bran (RAX and CAX), and their deferulyolated counterpart dRAX and dCAX were fermented using an in vitro fermentation model. Structural information was determined based on monosaccharide composition. Gas production of fermentation products, SCFAs production, pH change, and microbiota change were measured. Results RAX and dRAX posessed lower A/X ratio compared with CAX and dCAX. The gas and total SCFAs production were lower in RAX and dRAX, and the butyrate production were higher in RAX and dRAX compared with CAX and dCAX. Butyrate production was lower at dRAX compared to RAX. On the other hand, butyrate production was higher in dCAX than in CAX. The microbiota shift were different for the four fibers. Discussion The AXs from rice have a higher A/X ratio than the AXs from maize, suggesting more branching and a more complex side chain. The structural difference was crucial for the difference in fermentation pattern. Different Bacteroides species are responsible for the utilization of rice AXs and corn AXs. Although feruloylation had a minor effect on the overall fermentation pattern, it significantly affected butyrate production and alpha diversity. dRAX promoted less butyrate than RAX, which is associated with a significantly lower amount of Faecalibacterium prausnitzi. dCAX promoted more butyrate than CAX, which may be associated with a lower amount of Bacteroides ovatus and a higher amount of Blautia in dCAX compared to CAX. The effects of feruloylation on the fermentation pattern and the resulted microbiota shift of AX varied depending on the carbohydrate structure.